2023
DOI: 10.3389/fmicb.2023.1136845
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota facilitates adaptation of the plateau zokor (Myospalax baileyi) to the plateau living environment

Abstract: Gut microbiota not only helps the hosts to perform many key physiological functions such as food digestion, energy harvesting and immune regulation, but also influences host ecology and facilitates adaptation of the host to extreme environments. Plateau zokors epitomize successful physiological adaptation to their living environment in the face of the harsh environment characterized by low temperature, low pressure and hypoxia in the Tibetan plateau region and high concentrations of CO2 in their burrows. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Even more striking is the complete absence from our 16S dataset of the anaerobic bacterial genus Prevotella, which was previously found to be strongly associated with increasing altitude in wild house mice [47], wild pikas [109], high altitude yaks, in Tibetan sheep [110], and in humans [108,111], but see [106]. The Prevotella is also present at ~ 3.5% in subterranean plateau zokors -another member of the family Spalacidae living at high altitudes [112]. Our results as well as the previous studies suggest that the absence of Prevotella from BMR's GM may actually be a common feature of the wild populations of these rodents: i.e.…”
Section: Changes In Bacterial Taxa and Phenotypes Among The Altitudin...mentioning
confidence: 70%
“…Even more striking is the complete absence from our 16S dataset of the anaerobic bacterial genus Prevotella, which was previously found to be strongly associated with increasing altitude in wild house mice [47], wild pikas [109], high altitude yaks, in Tibetan sheep [110], and in humans [108,111], but see [106]. The Prevotella is also present at ~ 3.5% in subterranean plateau zokors -another member of the family Spalacidae living at high altitudes [112]. Our results as well as the previous studies suggest that the absence of Prevotella from BMR's GM may actually be a common feature of the wild populations of these rodents: i.e.…”
Section: Changes In Bacterial Taxa and Phenotypes Among The Altitudin...mentioning
confidence: 70%
“…The intestine harbors a diverse microbiota, comprising over 400 species of bacteria, with approximately 99% being obligate anaerobes ( Hu et al, 2023 ). The intestinal microbiota forms a mutualistic ecosystem, crucial for human health, constituting the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the composition of intestinal microbiota in populations living in different regions varies due to unique living environments, genetic backgrounds, or dietary habits ( Zhang et al, 2015 , 2018 ; Yadav et al, 2016 ; Geng et al, 2023 ; Hu et al, 2023 ). An Indian study investigated the composition of intestinal microbiota in healthy adults living in high-altitude and low-altitude regions ( das et al, 2018 ).…”
Section: The Changes In Intestinal Microbiota After Exposure To High-...mentioning
confidence: 99%